Report on Tobacco Control in the Region of the Americas 2018. (Pan American Health Organization (PAHO), 2018)
This new edition of the Report on Tobacco Control in the Region of the Americas describes the current situation and trends of the tobacco epidemic in the Region of the Americas. It includes contributions from guest experts who share their views on subjects of great interest to the Region, such as the Protocol to Eliminate Illicit Trade in Tobacco Products, regulation of new (and old) products, and lessons learned. The report also includes a Country Profiles section, which shows the status of implementation of the six MPOWER measures in each of the 35 Member States of the Region.